2021
DOI: 10.1136/bmjopen-2021-050672
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and daytime problems during the COVID-19 pandemic and effects of coronavirus infection, confinement and financial suffering: a multinational survey using a harmonised questionnaire

Abstract: ObjectivesSleep is important for human health and well-being. No previous study has assessed whether the COVID-19 pandemic impacts sleep and daytime function across the globe.MethodsThis large-scale international survey used a harmonised questionnaire. Fourteen countries participated during the period of May–August 2020. Sleep and daytime problems (poor sleep quality, sleep onset and maintenance problems, nightmares, hypnotic use, fatigue and excessive sleepiness) occurring ‘before’ and ‘during’ the pandemic w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
57
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 35 publications
7
57
0
6
Order By: Relevance
“…But not everybody is getting more sleep. In fact, many studies report insomnia, lower sleep quality, and more awakenings, which should reduce the total sleep time instead of increasing it [ 22 , 25 , 27 ].…”
Section: Making Sense Of Changed Dreamsmentioning
confidence: 99%
See 1 more Smart Citation
“…But not everybody is getting more sleep. In fact, many studies report insomnia, lower sleep quality, and more awakenings, which should reduce the total sleep time instead of increasing it [ 22 , 25 , 27 ].…”
Section: Making Sense Of Changed Dreamsmentioning
confidence: 99%
“…In a multinational study, worse sleep quality was found in about 20%, while better sleep quality was found in only 5% [ 25 ]. A study comparing sleep quality during and after a lockdown found that 46.07% reported low sleep quality during the lockdown.…”
Section: Making Sense Of Changed Dreamsmentioning
confidence: 99%
“…The COVID-19 pandemic and its consequences dramatically affected psychological well-being [ 1 , 2 ]. Moreover, many studies have documented the strong and complex effects of the pandemic on sleep pattern and their relationship with sociodemographic, environmental, and clinical variables [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Europa wurde 2020 eine multizentrische Fragebogenstudie initiiert, die nicht nur die Auswirkungen einer SARS-CoV-2-Infektion, sondern auch die Einflüsse des Lockdowns und damit zusammenhängender finanzieller Probleme auf diverse Schlafschwierigkeiten und die Verwendung von Hypnotika objektiviert hat [ 23 ]. Im Rahmen dieser Online-Befragungsstudie wurden die Daten von insgesamt 22.151 Teilnehmern ausgewertet.…”
Section: Pandemiestress Als Trigger Für Eine Insomnieunclassified